Vitamins in cell culture media: Stability and stabilization strategies. Issue 6 (21st February 2019) - Schnellbaecher, Alisa; Binder, Dennis; Bellmaine, Stephanie; Zimmer, Aline
Abstract: Nowadays, chemically defined cell culture media (CCM) have replaced serum‐ and hydrolysate‐based media that rely on complex ingredients, such as yeast extracts or peptones. Benefits include a significantly lower lot‐to‐lot variability, more efficient manufacturing by reduction to essential components, and the ability to exclude components that may negatively influence growth, viability, or productivity. Even though current chemically defined CCMs provide an excellent basis for various mammalian biotechnological processes, vitamin instabilities are known to be a key factor contributing to the variabilities still present in liquid CCM as well as to short storage times. In this review, the chemical degradation pathways and products for the most relevant vitamins for CCM will be discussed, with a focus on the effects of light, oxygen, heat, and other CCM compounds. Different approaches to stabilize vitamins in solution, such as replacement with analogs, encapsulation, or the addition of stabilizing compounds will also be reviewed. While these vitamins and vitamin stabilization approaches are presented here as particular for CCM, the application of these concepts can also be considered relevant for pharmaceutical, medical, and food supplement purposes. More precise knowledge regarding vitamin instabilities will contribute to stabilize future formulations and thus decrease residual lot‐to‐lot variability. Abstract : The use of chemically‐defined cell culture media in place of serum‐ or hydrolysate‐based media has significantly enhanced the robustness of cell culture in the biomanufacturing of therapeutic proteins. However, some of these essential chemical compounds, such as vitamins, still contribute to cell culture inconsistency via chemical degradation upon storage. This review highlights the likely chemical degradation pathways for vitamins in cell culture media, factors contributing to this degradation, and potential strategies to stabilize these vitamins in complex cell culture media.